ABU MANDOUR HILL IN ROSETTA THROUGH THE WRITINGS AND PAINTINGS OF EUROPEAN TRAVELERS - Sa'eed Saa'd Rakha (International Journal of Cultural Inheritance & Social Sciences ISSN: 2632-7597, 2019)
The writings of the early adventurous travelers who were able to reach Egypt in modern times were the magic factor in guiding those who followed them as adventurers and adventurers, for their passion for the history, effects, customs and traditions of this land. The earliest writings written by Western travelers to Egypt date back to the 13th century, mostly to clerics who accompanied the crusades, including a Swiss priest from Basel, Felix Fabry. In the early 19thcentury, after the French campaign 1798, and the world became aware of the Pharaonic civilization and the deciphering of the Rosetta stone and the ancient Egyptian language by Champollion in 1822, the traveler's journeys that described the city of Rosetta continued in detail. Abu Mandur Hill, located south of the city of Rosetta, includes the ruins of the Pharaonic city of Bolbitine, which continued to be built until Rosetta was established in the north. It was important that the research shed light on this important historical and historical site through the observations, writings and paintings of European travelers during the 18th and 19th centuries, who described this area accurately,And these travelers: Carsten Niebuhr, Charles Nicolas Sigisbert Sonnini de Manoncourt, Luigi Mayer, Dominique Vivant Denon, Jean-Baptiste Prosper Jollois.